An analysis of the necessity and relevance of establishing a pipeline regulator in South Africa's Petroleum Industry - Mutemeri, Gama (Energy Research Centre, 2019)
This thesis focuses on issues surrounding energy regulation, and specifically regulation of pipelines that carry petroleum products in South Africa. The introduction of a regulator for petroleum pipelines is part of an ongoing process taking center stage in the South African government's petroleum industry policy arena. Independent regulation of energy industries is a recent phenomenon in South Africa. There is much activity in deciding which regulatory models should be adopted in the energy sector. The thesis analyses a government policy decision to introduce a regulator of petroleum pipelines. Among some of the key issues that receive attention are the following: • Is the petroleum pipeline industry in South Africa large enough to justify an independent regulator? • Do pipelines in South Africa enjoy monopoly rents? If they do, is the establishment of an independent regulator the most cost-effective way of dealing with monopoly rents? • How effective would such a regulator be in the current structure of the country's petroleum industry? Road and rail transport systems carry vast quantities of petroleum products. Would it be more appropriate for the regulator to include all transporters of petroleum products? The thesis concludes that for an industry of such small size as pipeline transportation in South Africa, the necessity of a pipeline regulator might need to be reviewed. For a variety of reasons, there are strong reasons to conclude that a pipeline regulator will have minimum impact over key issues of the transportation of petroleum products.